Correlation Between Information Literacy and Critical Thinking Enhancement Through PjBL-Information Literacy Learning Model - Siti Supriyanti; Anna Permanasari; Fitri Khoerunnisa (Journal of Educational Sciences, 2020)
Information literacy is closely related to critical thinking skills. Critical thinking skills are related to exploring and evaluating information to make argumentation with relevant and appropriate information. It includes analyzing and synthesizing information to solve a problem where these activities are part of information literacy. Thus, information literacy-based learning should be able to enhance critical thinking skills. This study aims to determine the correlation between critical thinking skills and student’s information literacy enhancement through learning chemistry with the PjBL-IL model on the biogas production context. This study used a pre-experimental method - one group pretest-posttest design involving 32 high school students. Students' critical thinking and information literacy skills were measured using tests. Critical thinking skills and information literacy enhancement on high and medium category with N-gain score are 72.90% and 66.20% respectively and show a low correlation with a correlation coefficient value of 0.144. Where the basic support indicator has a negative correlation (r = -0.105). Thus, critical thinking skills enhancement is not always in line with information literacy.